A multicentre study to determine the in vitro efficacy of flomoxef against extended-spectrum beta-lactamase producing Escherichia coli in Malaysia - Yap, Polly Soo Xi; Ponnampalavanar, Sasheela; Tengku Zetty Maztura, Tengku Jamaluddin; Lee, Yee Qing; Lau, Min Yi (PeerJ Inc., 2023)
Background The high burden of extended-spectrum beta-lactamase-producing (ESBL)-producing Enterobacterales worldwide, especially in the densely populated South East Asia poses a significant threat to the global transmission of antibiotic resistance. Molecular surveillance of ESBL-producing pathogens in this region is vital for understanding the local epidemiology, informing treatment choices, and addressing the regional and global implications of antibiotic resistance. Methods Therefore, an inventory surveillance of the ESBL-Escherichia coli (ESBL-EC) isolates responsible for infections in Malaysian hospitals was conducted. Additionally, the in vitro efficacy of flomoxef and other established antibiotics against ESBL-EC was evaluated. Results A total of 127 non-repetitive ESBL-EC strains isolated from clinical samples were collected during a multicentre study performed in five representative Malaysian hospitals. Of all the isolates, 33.9 were isolated from surgical site infections and 85.8 were hospital-acquired infections. High rates of resistance to cefotaxime (100), cefepime (100), aztreonam (100) and trimethoprim-sulfamethoxazole (100) were observed based on the broth microdilution test. Carbapenems remained the most effective antibiotics against the ESBL-EC, followed by flomoxef. Antibiotic resistance genes were identified by PCR. The blaCTX-M-1 was the most prevalent ESBL gene, with 28 isolates (22) harbouring blaCTX-M-1 only, 27 isolates (21.3) co-harbouring blaCTX-M-1 and blaTEM, and ten isolates (7.9) co-harbouring blaCTX-M-1, blaTEM and blaSHV. A generalised linear model showed significant antibacterial activity of imipenem against different types of infection. Besides carbapenems, this study also demonstrated a satisfactory antibacterial activity of flomoxef (81.9) on ESBL-EC, regardless of the types of ESBL genes.